Identification of Durian Root Composition as A Compound that can Reduce Blood Sugar Levels - Sombuk, Hosiana Loisa; Sawasemariay, Oktoviandi; Nuryanti, Yayuk (Indonesian Journal of Global Health Research, 2024)
Durian is a fruit that can be used in the health sector. From the results of phytochemical tests, it was found that durian roots contain alkaloids, flavonoids, tannins, triterpenoids and saponins, each of which has functions as body metabolism, anti-oxidant, anti-bacterial, anti-diabetic, anti-microbial, hypocyclemia and glycogenesis. Some diabetes mellitus patients use durian root decoction regularly to lower blood sugar levels. Where diabetes mellitus (DM) is a chronic disease that occurs due to the pancreas not producing enough insulin or the body being unable to use the insulin produced effectively. The objective study to identify the composition of durian root as a compound that can lower blood sugar. This research uses a descriptive design. The research method involves conducting laboratory tests with graded solvent polarities according to the level of maceration extraction. The population and samples are durian roots that have been dried in the wind for 7 days. The research time will be September – November 2022 in the chemistry laboratory of the chemistry department, faculty of mathematics and natural sciences, University of Papua. The results of the phytochemical test for compounds contained in durian roots are alkaloids, flavonoids, tannins, triterpenoids and saponins. The compounds contained in durian roots are alkaloids, flavonoids, tannins, triterpenoids and saponins. Phytochemical test results of n-Hexane, Ethyl Acetate, Acetone, Ethanol and Aquades Extracts on Durian Roots; alkaloid test, flavonoid test, tannin test, triterpenoid test, saponin test, each of which has an influence on reducing blood sugar.